The measure of mind propositional attitudes and their attribution - Matthews, Robert J., 1943- (Oxford : Clarendon, 2007)
'The Measure of Mind' provides a sustained critique of a widely held view of beliefs, desires, and other 'propositional attitudes', according to which they are representations that play a causal role in the production of thought and behaviour.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Proposition (Logic)